2019
DOI: 10.1016/j.devcel.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Rho Flares Repair Local Tight Junction Leaks

Abstract: Graphical Abstract Highlights d ZnUMBA is a novel zinc-based ultrasensitive microscopic barrier assay d ZnUMBA detects transient, localized tight junction breaches in developing epithelia d Rho flares rapidly repair tight junctions to minimize leakiness at breach points d Actomyosin-mediated junction contraction promotes tight junction reinforcement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(136 citation statements)
references
References 66 publications
4
132
0
Order By: Relevance
“…Since these analyses assumed a constant pore length without any independent measurements, these conclusions must be regarded as tentative. We have observed that treatment of MDCK Type II renal epithelial cells with hydrogen peroxide, which increases Leak Pathway permeability, also increases cell twisting and movement (data not shown), similar to the effects of cell division described by Stephenson et al [125]. In this context, it is interesting to note the marked parallels between regulation of tight junction and adherens junction integrity.…”
Section: What Is the Leak Pathway?supporting
confidence: 83%
See 3 more Smart Citations
“…Since these analyses assumed a constant pore length without any independent measurements, these conclusions must be regarded as tentative. We have observed that treatment of MDCK Type II renal epithelial cells with hydrogen peroxide, which increases Leak Pathway permeability, also increases cell twisting and movement (data not shown), similar to the effects of cell division described by Stephenson et al [125]. In this context, it is interesting to note the marked parallels between regulation of tight junction and adherens junction integrity.…”
Section: What Is the Leak Pathway?supporting
confidence: 83%
“…It is likely that these localized regions may not exist on every cell at any single time point. Two recent studies demonstrating a small number of discrete sites where macromolecules cross the tight junction lend strong support for this concept of the Leak Pathway [124,125]. Stephenson et al [125] reported that sites of solute permeation were transient, remaining open for no more than 5 minutes.…”
Section: What Is the Leak Pathway?mentioning
confidence: 96%
See 2 more Smart Citations
“…As mentioned already, a hot spot to generate membrane protrusion was multicellular junctions where multiple bicellular junctions meet ( Fig. 2D), and the multicellular junctions are thought to be prone to disruption, as they receive tensile force from the bicellular junctions (Higashi and Miller, 2017;Stephenson et al, 2019). Such force is generated by contraction of junction-associated actomyosin, and therefore we examined whether there is any relation between myosin II activation and clamellipodia formation.…”
Section: Aj Disruption Induces Myosin II Activationmentioning
confidence: 93%